Modular pathway rewiring of Saccharomyces cerevisiae enables high-level production of L-ornithine - Qin, J.; Zhou, Y.; Krivoruchko, A.; Huang, M.; Liu, Lifang; Khoomrung, S.; Siewers, V.; Jiang, B.; Nielsen, J. (Nature Publishing Group, 2015)
Baker’s yeast Saccharomyces cerevisiae is an attractive cell factory for production of chemicals and biofuels. Many different products have been produced in this cell factory by reconstruction of heterologous biosynthetic pathways; however, endogenous metabolism by itself involves many metabolites of industrial interest, and de-regulation of endogenous pathways to ensure efficient carbon channelling to such metabolites is therefore of high interest. Furthermore, many of these may serve as precursors for the biosynthesis of complex natural products, and hence strains overproducing certain pathway intermediates can serve as platform cell factories for production of such products. Here we implement a modular pathway rewiring (MPR) strategy and demonstrate its use for pathway optimization resulting in high-level production of L-ornithine, an intermediate of L-arginine biosynthesis and a precursor metabolite for a range of different natural products. The MPR strategy involves rewiring of the urea cycle, subcellular trafficking engineering and pathway re-localization, and improving precursor supply either through attenuation of the Crabtree effect or through the use of controlled fed-batch fermentations, leading to an L-ornithine titre of 1,041±47 mg l−1 with a yield of 67 mg (g glucose)−1 in shake-flask cultures and a titre of 5.1 g l−1 in fed-batch cultivations. Our study represents the first comprehensive study on overproducing an amino-acid intermediate in yeast, and our results demonstrate the potential to use yeast more extensively for low-cost production of many high-value amino-acid-derived chemicals.